Estimating feral cat (Felis catus) density in a rural to urban gradient using camera trapping. Issue 3 (3rd July 2018) - Hansen, Cara M.; Paterson, Adrian M.; Ross, James G.; Ogilvie, Shaun C.
ABSTRACT: Control or eradication of feral cats ( Felis cattus ) is necessary for a number of reasons, including controlling zoonotic diseases and protecting native species in New Zealand. Estimating feral cat density provides vital information about location and logistical effort required for control operations but current methods used to estimate feral cat densities are often labour intensive and invasive, and may not provide appropriate baseline data. We determined the effectiveness of using camera traps to estimate a feral cat population compared with live-capture trapping in a semi-rural park. Camera trapping, with capture–recapture statistical modelling, was used to estimate population density of feral cats as between 1.06 and 1.19 cats/km 2 with an individual detection probability of 5.3% per camera/night. Camera trapping (seven individual feral cats identified) was a valuable addition to live trapping of feral cats (four cats live trapped) and provided a cost-effective, non-invasive and potentially more accurate tool for wildlife managers and researchers to measure feral cat densities.